Optimalisasi Pemenuhan Gizi Ibu Hamil Selama Ramadhan Melalui Edukasi di Wilayah Sungai Tiung - Erni Yuliastuti; Megawati; Efi Kristiana; Rafidah; Suryanti (Health Care : Journal of Community Service, 2026)
Optimizing the nutritional status of pregnant women is a national health priority in order to reduce maternal and infant mortality rates and prevent stunting. The Sungai Tiung area, which is under the jurisdiction of the Cempaka Community Health Center in Banjarbaru City, faces unique challenges during Ramadan, especially since fasting often conflicts with the physiological needs of pregnancy. Based on the situation data, this area has achieved 100% coverage for the first visit (K1), but there has been a decline in coverage for the sixth visit (k1), amounting to 53.9%, indicating a gap in terms of sustainability. The types of interventions carried out involved anthropometric screening to detect Chronic Energy Deficiency (CED) through Upper Arm Circumference (UAC) screening, structured education through leaflets, and evaluation through pre-test and post-test instruments. The screening results showed that there was a subpopulation of pregnant women with an ARM circumference of less than 23.5 cm who were more susceptible to complications such as Intrauterine Fetal Demise (IUFD). The evaluation results showed a significant increase in participants' awareness of balanced nutrition, namely 50% carbohydrates, 30% protein, and 10-20% fat, as well as fluid management of at least 2 liters. This educational activity was able to change the perception and behavior of pregnant women in meeting their nutritional needs to prevent CEM and obtain supervision during the fasting month to ensure the safety of the mother and fetus.